Characterizing differences in the muscle transcriptome between cattle with alternative LCORL-NCAPG haplotypes - Fernanda Martins Rodrigues; Leif E. Majeres; Anna C. Dilger; Joshua C. McCann; Christopher J. Cassady; Dan W. Shike; Jonathan E. Beever (BMC Genomics)
Abstract Background The LCORL-NCAPG locus is a major quantitative trait locus (QTL) on bovine chromosome 6 (BTA6) that influences growth and carcass composition in cattle. To further understand the molecular mechanism responsible for the phenotypic changes associated with this locus, twenty-four Charolais-sired calves were selected for muscle transcriptome analysis based on alternative homozygous LCORL-NCAPG haplotypes (i.e., 12 “QQ” and 12 “qq”, where “Q” is a haplotype harboring variation associated with increased growth). At 300 days of age, a biopsy of the longissimus dorsi muscle was collected from each animal for RNA sequencing. Results Gene expression analysis identified 733 genes as differentially expressed between QQ and qq animals (q-value < 0.05). Notably, LCORL and genes known to be important regulators of growth such as IGF2 were upregulated in QQ individuals, while genes associated with adiposity such as FASN and LEP were downregulated, reflecting the increase in lean growth associated with this locus. Gene set enrichment analysis demonstrated QQ individuals had downregulation of pathways associated with adipogenesis, alongside upregulation of transcripts for cellular machinery essential for protein synthesis and energy metabolism, particularly ribosomal and mitochondrial components. Conclusions The differences in the muscle transcriptome between QQ and qq animals imply that muscle hypertrophy may be metabolically favored over accumulation of fat in animals with the QQ haplotype. Our findings also suggest this haplotype could be linked to a difference in LCORL expression that potentially influences the downstream transcriptional effects observed, though further research will be needed to confirm the molecular mechanisms underlying the associated changes in phenotype.